11Digital Media. - Franklin, Seb (Year's Work in Critical & Cultural Theory, 2013)
This chapter reviews books and articles published in 2011. It is focused on texts that address the intersections of digital computation and the social and cultural formations of the historical period that has variously been named that of late capitalism, neoliberalism, post-Fordism and control societies.